Speech Acts in Migrant Nurses’ Clinical Interactions: Searle’s Classification and Bourdieu’s Interpretation - Nur Alfi Syahrin; Syihabuddin; Mahardhika Zifana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to identify the types of speech acts that emerge in interactions between Indonesian migrant nurse and her patients and colleagues in hospital environments. The research employs a single-case qualitative interview study using a pragmatic analysis approach. The participant was Indonesian migrant nurse working in hospital settings abroad. Data were collected through in-depth interviews to explore the nurse’ communicative experiences, and the data source consists of interview-based utterance excerpts rather than real-time recorded interactions. The data include utterances occurring between nurse and patients as well as between nurse and colleagues, as recalled by the participant. These utterances were analyzed and classified based on Searle’s speech act theory. The analysis identified 29 utterances: 12 assertive, 11 directive, 4 commissive, 2 expressive, and no declarative utterances. The findings were further interpreted using Bourdieu’s theoretical framework. The analysis demonstrates that speech acts function not merely as linguistic phenomena but as expressions of the nurse’ habitus, symbolic capital, and positioning within the healthcare field. Migrant nurse strategically use language to gain legitimacy, maintain professional authority, and negotiate power relations in clinical interactions. These findings contribute to a better understanding of migrant healthcare communication and offer practical implications for communication training and intercultural competence development in healthcare institutions.